Introducing Web Archives as a New Library Service: the Experience of the National Library of France - Aubry, Sara (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2010)
The collections held by the National Library of France (BnF) are part of the national heritage and include nearly 31 million documents of all types (books, journals, manuscripts, photographs, maps, etc.). New collection challenges have been posed by the emergence of the Internet. Within an international framework, the BnF is developing policy guidelines, workflows and tools to harvest relevant and representative segments of the French part of the Internet and organise their preservation and access. The Web archives of the French national domain were developed as a new service, released as a new application and made available to the public in April 2008. Since then, strategies have been and continue to be developed to involve librarians and reach out end users. This article will discuss the BnF experiment and will focus specifically on four issues: * collection building: Web archives as a new and challenging collection, * resource discovery: access services and tools for end users, * usage: facts and figures, * involvement: strategies to build a librarian community and reach out end users.